Clinical examples of 3D dose distribution reconstruction, based on the actual MLC leaves movement, for dynamic treatment techniques - Osewski, Wojciech (2014)
AIM: To present practical examples of our new algorithm for reconstruction of 3D dose distribution, based on the actual MLC leaf movement. BACKGROUND: DynaLog and RTplan files were used by DDcon software to prepare a new RTplan file for dose distribution reconstruction. MATERIALS AND METHODS: Four different clinically relevant scenarios were used to assess the feasibility of the proposed new approach: (1) Reconstruction of whole treatment sessions for prostate cancer; (2) Reconstruction of IMRT verification treatment plan; (3) Dose reconstruction in breast cancer; (4) Reconstruction of interrupted arc and complementary plan for an interrupted VMAT treatment session of prostate cancer. The applied reconstruction method was validated by comparing reconstructed and measured fluence maps. For all statistical analysis, the U Mann–Whitney test was used. RESULTS: In the first two and the fourth cases, there were no statistically significant differences between the planned and reconstructed dose distribution (p = 0.910, p = 0.975, p = 0.893, respectively). In the third case the differences were statistically significant (p = 0.015). Treatment plan had to be reconstructed. CONCLUSION: Developed dose distribution reconstruction algorithm presents a very useful QA tool. It provides means for 3D dose distribution verification in patient volume and allows to evaluate the influence of actual MLC leaf motion on the dose distribution.